Pengaruh Independensi, Pengalaman,Due Professional Care, Gender, dan Akuntabilitas Terhadap Kualitas Audit (Studi Empiris pada Kantor Akuntan Publik di Jawa Tengah dan Yogyakarta) - Juwono, Suhandono; , Drs. Agus Endro Suwarno, M.Si (2016)
Abstract This research aims to determine the effect of several factors that affect audit quality auditor at Public Accounting Office in Surakarta, Yogyakarta and Semarang. Factors examined in this paper are independence, experience, due professional care, gender and accountability. The research method used is quantitative data by using primary data obtained through the deployment quesioer. The population in this research is the auditor who works at Public Accounting Office in Surakarta, Yogyakarta and Semarang. The number of samples in this research were 120 respondents. Methods of sample collection using a convenience sampling technique. The analytical tool used include validity and reliability test, normality test, multicollinearity, heteroscedasticity test, multiple linear regression, f test, t test, and test the coefficient of determination (R2). Based on the results validity, reliability and classical assumption that the data obtained is good and no bias, so that it can continue multiple linear regression test. The test results of multiple regression showed that due professional care, gender, and accountability effect on audit quality. Where as the independence and experience make no significant effect on audit quality.